The Three Stooges collection. Volume one, 1934-1936 [videorecording (DVD)]. - Howard, Moe; Howard, Jerome Lester, 1903-1952; Fine, Larry (Three Stooges., 2016)
"When the Three Stooges first signed with Columbia Pictures, their deal was for one short. 1934's Woman Hater, done entirely in rhyme, wasn't a huge success, but the Stooges hit their stride with their second short, Punch Drunks, and began to settle into their definitive roles - Moe as boss, Larry the middleman and Curly as their foil. Witness the rise of these comedy icons in this high-spirited collection containing the first 10 Columbia shorts, all of which have been remastered for the best quality picture and sound. You'll experience the eye-pokes, face slaps, hollow head knocks and knuckle cracks like you've never heard or seen them before. So go ahead, nyuck yourself out!"--Jbhifi.com.au.